2012
DOI: 10.1104/pp.112.197228
|View full text |Cite
|
Sign up to set email alerts
|

Control of Pollen-Mediated Gene Flow in Transgenic Trees  

Abstract: Pollen elimination provides an effective containment method to reduce direct gene flow from transgenic trees to their wild relatives. Until now, only limited success has been achieved in controlling pollen production in trees. A pine (Pinus radiata) male cone-specific promoter, PrMC2, was used to drive modified barnase coding sequences (barnaseH102E, barnaseK27A, and barnaseE73G) in order to determine their effectiveness in pollen ablation. The expression cassette PrMC2-barnaseH102E was found to efficiently ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 38 publications
0
42
0
Order By: Relevance
“…Apparently, the only way of eliminating the risk of spread both outside and inside forest stands, would be by producing and planting sterile trees, which appears to be feasible, namely in Eucalyptus spp. (Zhang et al 2012). Indeed, Zhang et al (2012) showed that it is possible to prevent pollen formation in different transgenic plants, including eucalypts, without detrimental effects on vegetative growth.…”
Section: Management Considerationsmentioning
confidence: 95%
“…Apparently, the only way of eliminating the risk of spread both outside and inside forest stands, would be by producing and planting sterile trees, which appears to be feasible, namely in Eucalyptus spp. (Zhang et al 2012). Indeed, Zhang et al (2012) showed that it is possible to prevent pollen formation in different transgenic plants, including eucalypts, without detrimental effects on vegetative growth.…”
Section: Management Considerationsmentioning
confidence: 95%
“…Surprisingly, this occurred in spite of coexpression of the barnase inhibitor barstar (Wei et al 2006). In contrast, Zhang et al (2012) did not observe any growth impairment in their field-grown, male-sterile pines and eucalypts, possibly because of the reduced toxicity of the barnase variant employed. They did not, however, present any data or statistical analysis in support of this observation.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, Zhang et al (2012) reported complete male sterility over 4 years in pine and over 2 years in eucalypts. Tobacco and silver birch transformed with the BpMADS1::BARNASE and the BpFULL1::BARNASE constructs were highly sterile for three and two consecutive years, respectively (Lännenpää et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations